PENDAPATAN DAN TINGKAT KESEJAHTERAAN PETANI PISANG AMBON (Musa paradisiaca) DI KECAMATAN PADANG CERMIN KABUPATEN PESAWARAN - Edy Suyanto; Hurip Santoso; Rabiatul Adawiyah (Lampung University, 2014)
The purpose of this study was to determine: the amount of income of banana farmers and the level of banana farmers’ welfare. This research was conducted in Padang Cermin Village of Padang Cermin District, Pesawaran Regency. Respondents were 40 banana farmers chosen by using simple random sampling method. Data analysis used in this study is a quantitative and qualitative descriptive analysis. The results showed that, the amount of income of banana farmers in Padang Cermin village was Rp38,918,059.00 per year consisting of Rp29,945,659.95 per year (76.95%) from the banana farming, Rp7,088,400.95 per year or (18.21%) from farming other than banana, and the rest was from activities outside of farming, namely: Rp1,578,000.00 per year or (4.05%) from banana delivery service, Rp276,000.00 per year or (0.71%) from construction work, and Rp30,000.00 per year or (0.08%) from producing fermented soybean. Based on the criteria of Central Bureau of Statistics (BPS), as many as 37 banana farmer household respondents or (92.50%) in Padang Cermin village regency were categorized as prosperous and 3 banana farmers or (7.50%) were categorized as less prosperous. Keywords: Bananas, banana farmers, farmers’ income, welfare level